Coulson and Richardson's chemical engineering. - Ravi, R.; Vinu, R.; Gummadi, Sathyanarayana N.; Coulson, J. M. (John Metcalfe) (Butterworth-Heinemann is an imprint of Elsevier, 2017)
Coulson and Richardson's Chemical Engineering: Volume 3A: Chemical and Biochemical Reactors and Reaction Engineering, Fourth Edition, covers reactor design, flow modelling, gas-liquid and gas-solid reactions and reactors.